A home for loss: Doris Salcedo's melancholic archives. (April 2015) - Lauzon, Claudette
This article considers the art practice of Bogotá-based sculptor Doris Salcedo, whose work has primarily involved transforming testimonies of political violence in Colombia into abstracted assemblages that bear witness to suffering and loss. Melancholic archives that cling to their capacity to accommodate what remains of loss but also recognise their own structural provisionality, Salcedo's sculptures and installations represent a process of excavation and archivisation that, by failing to coalesce into sites of closure or redemption, disclose art's capacity to unsettle our collective access to the past while insisting nevertheless on bearing witness to the suffering of others. Radically reconsidering the archive's putative status as a 'home' for memory, Salcedo's practice at the same time figures home as an (impossible) archive for memories of loss, terror and displacement.